Numerical investigation of the cold-formed I-beams bending strength with different web shapes (Fracture and Structural Integrity, 2021)
The wide use of cold-formed sections (CFS) in the field of steel constructions, favored by the multiple advantages they offer (lightness, ease of installation, etc.), has led us to reflect on a new process for manufacture of metal beams allowing the design of very large span hangars and a reduction in instability problems. This paper presents a study of the theoretical and numerical behavior of a large span CFS beam with different webs, a solid web, a triangular corrugated web, and a trapezoidal corrugated web. These beams are stressed by a concentrated bending load at mid-span. Numerical modeling was done using the finite element software ABAQUS. The results were validated with those theoretically found, based on the effective width method adopted in standard EN1993-1-3. The load capacity and failure modes of the beams were discussed. According to numerical and analytical analysis, corrugated web beams perform better than all other sections.
Keywords: Cold formed sections; Corrugated webs; Finite element models; Bending test; Failure modes